Role of Antarctic ozone in shaping East Asian summer precipitation variability - Lingaona Zhu; Zhiwei Wu; Bin Wang (npj Climate and Atmospheric Science)
Abstract Most previous studies on the climatic effects of Antarctic ozone have focused primarily on the Southern Hemisphere. This study suggests that September-October Antarctic ozone anomalies account for approximately 12% of the interannual variability in East Asian summer precipitation. The precipitation anomalies linked to the Antarctic ozone index are characterized by increased rainfall between the Yangtze and Yellow Rivers in central East China and decreased rainfall over Southeastern China. Our analysis reveals that positive Antarctic ozone anomalies during September–October are associated with a negative phase of the Southern Annular Mode (SAM) during the subsequent boreal winter. The resulting SAM-related circulation anomalies exert a significant influence on sea surface temperature anomalies (SSTAs) in the southwestern Indian Ocean, particularly near the Madagascar region. Owing to the ocean’s thermal inertia, these SSTAs persist into the subsequent boreal spring, altering the meridional circulation and leading to anomalous subsidence near 15°N, which in turn results in elevated skin temperature anomalies (SKTAs) over the Indochina Peninsula. Numerical experiments conducted with the Community Atmospheric Model version 5 further confirm the role of southwestern Indian Ocean SSTAs in driving this response. Land memory and positive land–atmosphere feedbacks sustain these SKTAs into boreal summer. Consequently, the SKTAs-induced heating over the Indochina Peninsula enhances the southwesterly monsoon and strengthens precipitation over central East China, as demonstrated by linear baroclinic model experiments. Furthermore, the Specified-Chemistry version of the Whole Atmosphere Community Climate Model is used to verify the remote influence of Antarctic ozone anomalies on East Asian summer precipitation. Our findings provide an additional predictor for summer precipitation over East Asia and deepen our understanding of the interhemispheric impacts of Antarctic ozone.